Analyzing The Impact of Import Tariff Policy on Indonesia’s Economy: An Ibnu Khaldun Fiscal Framework - Sitti Aisyah; Nurul Huda (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
This study analyses the import tariff policy implemented by Donald Trump, specifically the initial 32% tariff on Indonesia that was later negotiated down to 19%, and its subsequent impact on the Indonesian economy as seen through the lens of Ibnu Khaldun. The policy aims to protect the U.S. domestic industry and reduce the trade deficit; however, it has significant implications for trading partner countries, including a decline in export competitiveness, the risk of layoffs, and potential trade imbalances. This study employs a qualitative approach and a literature review method. The primary data source is Ibn Khaldun's Muqaddimah, and secondary data is obtained from scientific journals, economic reports, and reliable media outlets. Content analysis is used to link the concepts of tax (al-jibayah), the cycle of civilization, and the fiscal burden in Ibn Khaldun's thinking with the reality of contemporary import tariff policies. The results show that, although reducing tariffs from 32% to 19% mitigated the short-term socioeconomic impact, including the threat of mass layoffs, these tariffs contradict Ibn Khaldun's fiscal principles. His principles emphasize light taxation, fairness, and efficiency to encourage economic productivity. High tariffs have the potential to weaken trade activity, hinder industrial growth, and create structural dependence.